Psychological Dynamics of Person with Residual Type of Paranoid Schizophrenia: Dinamika Psikologis Kasus Individu dengan Schizophrenia Paranoid Tipe Residual - Farisandy, Ellyana Dwi (Psikologia : Jurnal Psikologi, 2019)
Schizophrenia is one of the most common mental disorders and is increasing every year. One common type of schizophrenia is paranoid schizophrenia. Usually, a positive symptom that often appears in paranoid schizophrenia is auditory hallucinations. Furthermore, paranoid schizophrenia residual type is an end stage of schizophrenia disorder where the individual does not have positive symptoms but still experiences some negative symptoms. The method used in this research is qualitative namely case studies. This case study aims to describe the assessment, diagnosis, and psychological dynamics of individuals who have residual paranoid type schizophrenia. Participant is one person selected using purposive sampling. Data mining is done by conducting interviews, observations, and psychological tests. Interviews were conducted both to the subject and significant others. Observation and psychological tests conducted on the subject. Psychological tests provided include intelligence and personality tests. The results obtained that AS does not have positive symptoms. However, negative symptoms that are still felt are subject who has confusion, has difficulty in controlling emotions and does not want to work. In addition, the psychological dynamic of AS is he has experienced many traumatic events in his life, including: death from his family, repeated fraud, not getting appreciation from the environment and he who felt that his role as head of the family could not function properly.